Korzika - gorati sredozemski otok - Gumilar, Andreja (Geografski obzornik, 2003)
Corsica is a mountainous island in the Mediterranean belonging to France. It is a popular holiday destination offering mountaineering, hill walking, sunbathing on its many beaches and water sports. Its strategic position in the centre of the ancient world attracted numerous foreign conquerors. This has made the Corsicans a proud people who still yearn for independence.
Keywords: domoznanstvo; Korzika; regionalna geografija; zgodovina